Heck reaction in ionic liquid accelerated by microwave irradiation / Siti Zarina Mohd Sali - Mohd Sali, Siti Zarina (2008)
This research aims at investigating Heck reaction in ionic liquid accelerated by microwave irradiation. Five different conditions have been utilized in order to accomplish this research study. Three of the conditions utililized Heck reaction in ionic liquids and other two conditions utilized heck reaction in ionic liquids accelerated by microwave irradiation. When Heck reaction in ionic liquids, the desired stilbene able to produced with the yield 26.3% (with 4-iodoanisole as starting materials for 12 hours) and 33.85% (with 4-Iodophenylbenzyl ether as starting materials for I 2 hours) and 7.98% (with 4-iodoanisole as starting materials leave for 21 hour). While when Heck reaction accelerated by microwave irradiation, the desired stilbene able to produced with the yield 61.35% ( with the ionic liquids) and 68.27% (with DMF). Preparative TLC were used to confirm the desired product.